Pengaruh Budaya Kerja Agen Perubahan Terhadap Perilaku Birokrasi di Kecamatan Padang Utara Kota Padang - Harvi Dasnoer; Aldri Frinaldi; Syamsir Syamsir (Peneliti.net, 2023)
The Municipal Government of Padang through North Padang District continues to make changes and developments in governance through bureaucratic reform. There are 8 areas of change in bureaucratic reform that need to be carried out seriously and sustainably. One of the important areas of change is a change in mindset and culture set (work culture). Mayor of Padang Decree Number 274 of 2019 concerning Bureaucratic Reform Change Agents for the Padang City Government assigns individuals or groups of organizational members from the leadership level to employees to be able to drive change in the work environment and at the same time act as role models for each individual organization. This study analyzes the influence of the work culture of change agents on the behavior of bureaucratic apparatus using a descriptive quantitative approach and the population is all State Civil Servants of the North Padang District with a total of 71 people based on the bezzeting of this District in December 2022. Data collection with this questionnaire starts from distribution until all questionnaires were collected again in full took place from October to December 2022. This questionnaire was prepared according to a Likert scale which was made based on the Padang Mayor Regulation Number 18 of 2016 concerning Guidelines for the Development of Change Agents. Based on this research data, it can be seen that the work culture of change agents has an influence significant and contributed 17.4% while the remaining 82.6% was influenced by other variables not examined in this study. Keywords: Work culture, Agent of Change, Bureaucratic behavior